Seasonal patterns of Asthma medication fills among diverse populations of the United States. (3rd July 2018) - Turi, Kedir N.; Gebretsadik, Tebeb; Lee, Rees L.; Hartert, Tina V.; Evans, Amber M.; Stone, Cosby; Sicignano, Nicholas M.; Wu, Ann C; Iribarren, Carlos; Butler, Melissa G.; Mitchel, Edward; Morrow, James; et al.
ABSTRACT: Objective : Nonadherence to controller and overuse of reliever asthma medications are associated with exacerbations. We aimed to determine patterns of seasonal asthma medication use and to identify time period(s) during which interventions to improve medication adherence could reduce asthma morbidity. Methods : We conducted a retrospective cohort study of asthmatics 4–50 years of age and enrolled in three diverse health insurance plans. Seasonal patterns of medications were reported by monthly prescription fill rates per 1000 individuals with asthma from 1998 to 2013, and stratified by healthcare plan, sex, and age. Results : There was a distinct and consistent seasonal fill pattern for all asthma medications. The lowest fill rate was observed in the month of July. Fills increased in the autumn and remained high throughout the winter and spring. Compared with the month of May with high medication fills, July represented a relative decrease of fills ranging from 13% (rate ratio, RR: 0.87, 95% confidence interval, 95%CI: 0.72–1.04) for the combination of inhaled corticosteroids (ICS) + long acting beta agonists (LABA) to 45% (RR: 0.55, 95%CI: 0.49–0.61) for oral corticosteroids. Such a seasonal pattern was observed each year across the 16-year study period, among healthcare plans, sexes, and ages. LABA containing control medication (ICS+LABA and LABA) fill rates were more prevalent in older asthmatics, while leukotriene receptor antagonists were more prevalent in the younger population. Conclusions : A seasonal pattern of asthma medication fill rates likely represents a reactive response to a loss of disease control and increased symptoms. Adherence to and consistent use of asthma medications among individuals who use medications in reaction to seasonal exacerbations might be a key component in reducing the risk of asthma exacerbations.